Data analysis & decision making with Microsoft Excel - Albright, S. Christian (Thomson/South-Western, 2006)
Master data analysis, modeling, and spreadsheet use with "Data Analysis & Decision Making with Microsoft Excel" With a teach-by-example approach, student-friendly writing style, and complete Excel integration, this quantitative methods text provides you with the tools you need to succeed. Margin notes, boxed-in definitions and formulas in the text, enhanced explanations in the text itself, and stated objectives for the examples found throughout the text make studying easy. Problem sets and cases provide realistic examples that enable you to see the relevance of the material to your future as a business leader. The CD-ROMs packaged with every new book include the following add-ins: the Palisade Decision Tools Suite (@RISK, StatTools, PrecisionTree, TopRank, and RISKOptimizer); and SolverTable, which allows you to do sensitivity analysis. All of these add-ins have been revised for Excel 2007.